RETRACTED: NeuroSuites: An online platform for running neuroscience, statistical, and machine learning tools - Moreno-Rodríguez, José Luis; Larrañaga, Pedro; Bielza, Concha (Frontiers in Neuroinformatics, 2023)
Problems with large amounts of data are common in the field of neuroscience. Specific machine learning and statistical tools are then required to transform the data into useful knowledge. In this work we present NeuroSuites, an easy-access web platform with its own architecture that we developed. NeuroSuites has different software tools to integrate statistical data analysis and machine learning algorithms commonly used in neuroscience applications. The list of available software tools will be expanded in future updates, enabled by the scalability of the NeuroSuites architecture.